Pouch excision: indications and outcomes. (3rd October 2017) - Lightner, A. L.; Dattani, S.; Dozois, E. J.; Moncrief, S. B.; Pemberton, J. H.; Mathis, K. L.
Abstract: Aim: Restorative proctocolectomy with ileal‐pouch anal anastomosis is the procedure of choice for ulcerative colitis. Unfortunately, up to 10% of pouches will fail, requiring either reconstruction or excision. While several series have reported on the aetiology of pouch failure, no study to date has focused on the postoperative complications associated with pouch excision. Methods: Patients who had excision of ileoanal reservoir with ileostomy (CPT code 45136) were included. Data abstracted included preoperative, operative and postoperative variables. A Kaplan–Meier curve of pouch survival was performed. Results: In all, 147 patients met the inclusion criteria for the study. The median age of patients was 47 years (73 women), and 132 had a diagnosis of ulcerative colitis at the time of colectomy. The most common indications for pouch excision were sepsis ( n = 46; 31%) and Crohn's disease ( n = 37; 25%). 84 (57%) patients experienced short‐term (< 30 days) postoperative complications, the most common of which was a surgical site infection ( n = 32; 21%); 55 (37%) patients had long‐term complications (> 30 days) postoperatively, the most common of which was a return to the operating room ( n = 19; 13%) largely for perineal wounds. Thirty‐day mortality was zero. 4.8%, 47.6%, 65.3% and 84.4% of patients had undergone pouch excision by 1, 5, 10 and 20 years from the time of pouch construction, respectively. Conclusions: Pouch excision has a high rate of both short‐ and long‐term postoperative complications. Patients should be appropriately counselled to set expectations accordingly. In view of these findings we suggest that this operation should ideally be performed at a high volume centre with the availability of a multidisciplinary surgical team.